Emerging roles of platelets in cancer biology and their potential as therapeutic targets - Wang, Lei; Wang, Xueying; Guo, Erliang; Mao, Xionghui; Miao, Susheng (Frontiers in Oncology, 2022)
The main role of platelets is to control bleeding and repair vascular damage. They also promote tumor metastasis through platelet-tumor cell interactions, which have been implicated in the mechanism of thrombosis. Platelet-tumor cell interactions promote tumor cell survival and dissemination in the circulation. Tumor cells can induce platelet activation and alter platelet RNA profiles. Liquid biopsies based on tumor-educated platelet biomarkers can detect tumors and correlate with prognosis, personalized therapy, treatment monitoring, and recurrence prediction. Platelet-based strategies for cancer prevention and tumor-targeted therapy include developing drugs that target platelet receptors, interfere with the release of platelet particles, inhibit platelet-specific enzymes, and utilize platelet-derived "nano-platelets" as a targeted drug delivery platform for tumor therapy. This review elaborates on platelet-tumor cell interactions and the molecular mechanisms and discusses future research directions for platelet-based liquid biopsy techniques and platelet-targeted anti-tumor strategies.